3-D Tomographic Model Inferred From Broadband Seismological Data At Hengill Geothermal Field (Iceland) - Jousset, Philippe (Zenodo, 2008)
This report describes the processing carried out to retrieve data from the disks and describes algorithms used in order to extract significant information from data about the seismic activity at the Hengill geothermal field and the neighbouring volcanic complex. The data set consists of broadband seismological data form the IGET network and from 3 stations of the SIL network, allowing us a more accurate analysis of the seismic activity within the area. We performed: • detection and classification of recorded seismicity • improvement of hypocenter locations and structural features of the geothermal system by tomography techniques : ENGINE - FP6